2021
DOI: 10.1007/s00442-021-04850-w
|View full text |Cite
|
Sign up to set email alerts
|

Individuality counts: A new comprehensive approach to foraging strategies of a tropical marine predator

Abstract: Foraging strategies are of great ecological interest, as they have a strong impact on the fitness of an individual and can affect its ability to cope with a changing environment. Recent studies on foraging strategies show a higher complexity than previously thought due to intraspecific variability. To reliably identify foraging strategies and describe the different foraging niches they allow individual animals to realize, high-resolution multivariate approaches which consider individual variation are required.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 66 publications
0
27
0
Order By: Relevance
“…These differences may be due to divergent behavioural traits among individual seals (Toscano et al, 2016;Troxell-Smith and Mella, 2017). Individual behavioural traits under-pins differences in foraging behaviour in other species (Patrick et al, 2014;Toscano et al, 2016;Krüger et al, 2019;DiNuzzo and Griffen, 2020;Steinhoff et al, 2020), and distinct, stable foraging strategies have been identified in many pinnipeds [e.g., Australian sea lions, Neophoca cinerea (Lowther et al, 2011); Galapagos sea lions, Zalophus wollebaeki (Villegas-Amtmann et al, 2008)], consistent with individual traits (Schwarz et al, 2021). In dynamic environments, multiple foraging strategies within a population may reduce resource competition (Lewis et al, 2006;Baylis et al, 2015).…”
Section: Individual Variabilitymentioning
confidence: 84%
“…These differences may be due to divergent behavioural traits among individual seals (Toscano et al, 2016;Troxell-Smith and Mella, 2017). Individual behavioural traits under-pins differences in foraging behaviour in other species (Patrick et al, 2014;Toscano et al, 2016;Krüger et al, 2019;DiNuzzo and Griffen, 2020;Steinhoff et al, 2020), and distinct, stable foraging strategies have been identified in many pinnipeds [e.g., Australian sea lions, Neophoca cinerea (Lowther et al, 2011); Galapagos sea lions, Zalophus wollebaeki (Villegas-Amtmann et al, 2008)], consistent with individual traits (Schwarz et al, 2021). In dynamic environments, multiple foraging strategies within a population may reduce resource competition (Lewis et al, 2006;Baylis et al, 2015).…”
Section: Individual Variabilitymentioning
confidence: 84%
“…active and inactive) 5 . HMMs have accordingly been used to analyse animal tracking data in relation to, among others, environmental conditions 52 , anthropogenic activity 53 , sex 54 , ontogeny 55 , and individualised niches 56 .…”
Section: Methodsmentioning
confidence: 99%
“…This closely resembles the benthic diver strategy in the GSL, where benthic divers have higher CORT levels and return repeatably to the same shallow foraging areas which are considered a more reliable habitat but one with lower prey density and quality (Schwarz et al, 2021). Reliability is inferred because the quantity of benthic prey in GSL diets is more common when environmental conditions (e.g., sea surface temperatures) become suboptimal (Páez-Rosas et al, 2020).…”
Section: Cortisol Test and Potential Links To Risk Assessmentmentioning
confidence: 64%
“…Here, pelagic divers, with greater depths, durations, and total dive times, had significantly higher thyroid T3 levels than their night diving counterparts. As seen in Schwarz et al (2021), night divers exhibit quite diverse and unique behavior in that they mostly taking shallow dives of ~30-60 m with shorter durations compared to pelagic divers. Although night divers are known to show flexibility and occasionally take deeper foraging bouts during the day, they mostly exploit mesopelagic prey that overlap with the shallow pelagic zone at night.…”
Section: Hormonal Effects On Energy Mobilization?mentioning
confidence: 99%